2009
DOI: 10.2353/ajpath.2009.080731
|View full text |Cite
|
Sign up to set email alerts
|

Low-Level Expression of MicroRNAs let-7d and miR-205 Are Prognostic Markers of Head and Neck Squamous Cell Carcinoma

Abstract: Small noncoding microRNAs (miRNAs) have been shown to be abnormally expressed in every tumor type examined. The importance of miRNAs as potential cancer prognostic indicators is underscored by their involvement in the regulation of basic cellular processes such as cell proliferation, differentiation, and apoptosis. In this study, miRNA expression profiles of head and neck squamous cell carcinoma (HNSCC) tumor and adjacent normal tissue were examined by microarray analysis and validated by quantitative TaqMan r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
276
1
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 328 publications
(297 citation statements)
references
References 41 publications
18
276
1
2
Order By: Relevance
“…ARF4 interacts with EGFR, thereby enhancing oncogenic processes. 47 On the other hand, the loss of hsa-miR-205 shown in malignant prostate tissue in our study (Table 2) and by others 11 as well as in other cancer types 48,49 is suggested a hallmark of epithelial-mesenchymal transition. Hsa-miR-205 targets SIP1 and ZEP which promote this transition.…”
Section: Discussionmentioning
confidence: 57%
“…ARF4 interacts with EGFR, thereby enhancing oncogenic processes. 47 On the other hand, the loss of hsa-miR-205 shown in malignant prostate tissue in our study (Table 2) and by others 11 as well as in other cancer types 48,49 is suggested a hallmark of epithelial-mesenchymal transition. Hsa-miR-205 targets SIP1 and ZEP which promote this transition.…”
Section: Discussionmentioning
confidence: 57%
“…We found that hsamiR-21 was higher in tumor than normal tissue, in keeping with previous studies showing its overexpression in HNSCC. 23 hsa-miR-10b expression was lower in tumor than normal tissue, again in keeping with our previous result in breast cancer, 32 and that of Childs et al in HNSCC, 33 but conflicting with the finding of Ma et al 18 Given our previous finding that the adjacent normal tissue had a lower hypoxia score by metagene than its matched tumor, 7 we were expecting that hsa-miR-210 would be lower in normal than in tumor tissue. However, for hsamiR-210, expression in some tumors was higher than matched normal tissue, and expression in others was lower.…”
Section: Discussionmentioning
confidence: 58%
“…MiR-205 might also regulate EMT by targeting ZEB1 and SIP1 in collaboration with miR-200 family miRNA including miR-200c (16,18) and target the HER3 oncogene in human breast cancer. (45) It has recently been reported that low-level expression of miR-205 is a prognostic marker of HNSCC, (46) and that downregulation of microRNA of the miR-200 family and miR-205 and an altered expression of classic and desmosomal cadherins were observed in spindle cell carcinoma of the head and neck with EMT. (47) Therefore, in addition to miR-200c, downregulation of miR-205 after HGF stimulation might also play an important role in progression of HNSCC with EMT.…”
Section: Discussionmentioning
confidence: 99%